2017
DOI: 10.3892/mmr.2017.8277
|View full text |Cite
|
Sign up to set email alerts
|

Time-course behavioral features are correlated with Parkinson's disease‑associated pathology in a 6-hydroxydopamine hemiparkinsonian rat model

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative diseases. For decades, the unilateral 6-hydroxydopamine (6-OHDA) rat model has been employed to investigate the pathogenesis and therapy of PD. However, the behavior and associated pathological features of the model long term have not previously been described dynamically. In the present study, the unilateral model was established by 6-OHDA injection in the striatum. The PD rat model was determined 2 weeks following surgery, according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
6
37
0
Order By: Relevance
“…We found that 6-OHDA treatment induced behavioral deficits in mice, such as a reduction in spontaneous motor behavior and motor incoordination, and these behavioral alterations were consistent with previous reports (Su et al, 2018 ). Behavioral impairments observed in the 6-OHDA-induced animal model of PD correlated with nigrostriatal neurodegeneration and depletion of DA and metabolites in the striatum.…”
Section: Discussionsupporting
confidence: 93%
“…We found that 6-OHDA treatment induced behavioral deficits in mice, such as a reduction in spontaneous motor behavior and motor incoordination, and these behavioral alterations were consistent with previous reports (Su et al, 2018 ). Behavioral impairments observed in the 6-OHDA-induced animal model of PD correlated with nigrostriatal neurodegeneration and depletion of DA and metabolites in the striatum.…”
Section: Discussionsupporting
confidence: 93%
“…In the pathogenesis, astrocytes are critical in initiating and perpetuating inflammatory process associated with PD. PD significantly increases the expression of GFAP as shown in primary cultured astrocytes (Yu et al, 2018) and in the substantia nigra pars compacta of rats (Su et al, 2018). In lipopolyscharride-evoked PD model, impairment of motor function and memory is accompanied with increased GFAP expression as well as enhanced expressions of α-synuclein, amyloid-β and p-Tau and reduced tyrosine hydroxylase (Zhang & Xu, 2018).…”
Section: Parkinson's Diseasementioning
confidence: 95%
“…Indeed, it is common to wait three weeks after surgery for a stable nigrostriatal lesion development before using the lesioned animals for further analyses [8,[34][35][36][37]. The most prominent deficits reported for the 6-OHDA-injected models are asymmetries in sensorimotor reactivity starting from 6 weeks [8], posture over 19 weeks [35], impairments of motor coordination and balance skills starting from 2 weeks [10] after lesion. In a recent study, combining PET imaging and Catwalk gait analysis 4 weeks after 6-OHDA lesion in the MFB, it was shown that altered brain metabolism and gait abnormalities correlate with DAergic lesion severity in the rat, indicating that striatal DA depletion, focal changes of glucose metabolism, and motor impairments are strongly linked [38].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models have been employed in experimental studies concerning the pathogenetic mechanism of PD and therapeutic strategies [5]. The classical unilateral 6-hydroxydopamine (6-OHDA) model, showing PD-associated pathological and behavioral features, is considered one of the most useful tools in PD research [6][7][8][9][10]. Over the years, to lesion the mesencephalic dopamine (DA) neurons and reproduce, to some degree, PD motor impairments, different concentrations of 6-OHDA have been infused either into the SNc, medial forebrain bundle (MFB), or the ST, leading to partial or complete neurodegeneration [7,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation